Roles of membrane trafficking in nerve repair and regeneration - Tuck, Elizabeth (Landes Bioscience, 2010)
Successful axonal repair following injury is critical for nerve regeneration and functional recovery. Nerve repair relies on three functionally distinct events involving membrane trafficking. First, axonally transported vesicles accumulate, while others are generated at the cut end to restore a selective barrier to the severed axon. Then, retrograde transport of vesicles along microtubules informs the cell body that damage has occurred in the distal axon. Finally, membrane addition to a newly formed growth cone, or to the axonal membrane is required to promote axonal re-growth and elongation. Yet, how these membrane trafficking events are regulated and what are the identities of the molecules and organelles involved remains largely unknown. Several potential factors have been recently identified. Members of the SNARE machinery appear to regulate fusion of vesicles in a calcium-dependent manner to promote axolemmal resealing. Retrograde transport of endosomes powered by the dynein-dynactin molecular motor complex represents a potential injury-signaling platform. Several classes of secretory and endocytic vesicles may coordinate axonal membrane extension and re-growth. Here we discuss recent advances in understanding the mechanisms of the membrane trafficking involved in nerve repair.